2013
DOI: 10.1021/am401285x
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid-Functionalized Core–Shell–Shell Magnetic Composite Microspheres for the Selective Enrichment of Glycoprotein

Abstract: In this work, core-shell-shell-structured boronic acid-functionalized magnetic composite microspheres Fe3O4@SiO2@poly (methyl methacrylate-co-4-vinylphenylbornoic acid) (Fe3O4@SiO2@P(MMA-co-VPBA)) with a uniform size and fine morphology were synthesized. Here, Fe3O4 magnetic particles were prepared by a solvothermal reaction, whereas the Fe3O4@SiO2 microspheres with a core-shell structure were obtained by a sol-gel process. 3-(Trimethoxysilyl) propyl methacrylate (MPS)-modified Fe3O4@SiO2 was used as the seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 43 publications
0
60
2
Order By: Relevance
“…S3 and revealed that the amount of OVA bound to the beads at equilibrium, Q , increased as the initial concentration of OVA increased. The static absorption data showed that the beads possessed a higher binding capacity for the analyte, and the maximum adsorption content was 31.4 mg/g in the OVA concentration range of 0.08–1.0 mg/mL, which was higher than other boronated materials .…”
Section: Resultsmentioning
confidence: 90%
“…S3 and revealed that the amount of OVA bound to the beads at equilibrium, Q , increased as the initial concentration of OVA increased. The static absorption data showed that the beads possessed a higher binding capacity for the analyte, and the maximum adsorption content was 31.4 mg/g in the OVA concentration range of 0.08–1.0 mg/mL, which was higher than other boronated materials .…”
Section: Resultsmentioning
confidence: 90%
“…Fe 3 O 4 @SiO 2 MNPs were synthesized by Stöber method according to the previous researches [13,16]. Fe 3 O 4 (1.2 g) was homogeneously dispersed in the mixture of anhydrous ethanol (400 mL), ultrapure water (200 mL), and ammonia solution (6 mL).…”
Section: Methodsmentioning
confidence: 99%
“…First, the Fe 3 O 4 nanoparticles were prepared though a hydrothermal method ( Figure 1 a). [ 41 ] These nanoparticles had a hydrodynamic diameter of 221 nm and polydisperse index (PDI) of 0.21 measured by DLS (Figure 1 d). The uniformity of these nanoparticles as the cores was responsible of the size distribution of the fi nal naorattles.…”
Section: Preparation and Characterization Of Fe 3 O 4 @Msio 2 Nanorattlementioning
confidence: 98%